Pengembangan Sistem Kalender Kerja Berbasis Website untuk Meningkatkan Efisiensi Pengelolaan Jadwal pada Bps Kota Kendari - Aqsan, La ode Pali; Ananda, Muh. Rezky; Wulandari, Suci; Aksara, LM Fid; ., Isnawaty (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
The Central Statistics Agency (BPS) of Kendari City plays a crucial role in statistical data management to support decision-making. Despite operational activities, employee work schedules are still managed manually, leading to a number of challenges, including delays in information processing, scheduling conflicts, and a lack of transparency. The main focus of this research is the development of an online work calendar system to support the efficiency and effectiveness of operational schedule management at BPS Kendari City. This system provides features such as daily, weekly, and monthly scheduling, automatic task reminder notifications, and reports that management can use to monitor employee activities. The development method used is the Waterfall model. The system development process includes several main stages: needs identification, design, implementation, testing, and comprehensive evaluation. The trials conducted showed that this system successfully improved the efficiency of work schedule management. The test results showed that the system was able to improve schedule management efficiency, minimize time conflicts, and improve internal coordination between employees. With the implementation of this system, it is hoped that BPS Kendari City can improve organizational performance and contribute to the creation of a more modern and technology-integrated government system.